A 4-Week Model of House Dust Mite (HDM) Induced Allergic Airways Inflammation with Airway Remodeling - L. N. Woo (Nature Portfolio, 2018)
Abstract Animal models of allergic airways inflammation are useful tools in studying the pathogenesis of asthma and potential therapeutic interventions. The different allergic airways inflammation models available to date employ varying doses, frequency, duration and types of allergen, which lead to the development of different features of asthma; showing varying degrees of airways inflammation and hyper-responsiveness (AHR) and airways remodeling. Models that also exhibit airway remodeling, a key feature of asthma, in addition to AHR and airway inflammation typically require 5–12 weeks to develop. In this report, we describe a 4-week mouse model of house dust mite (HDM)-induced allergic airways inflammation, and compare the phenotypic features of two different doses of HDM exposures (10 µg and 25 µg) for 5 days/week with a well-characterized 8-week chronic HDM model. We found that 4 weeks of intranasal HDM (25 µg in 35 µl saline; 5 days/week) resulted in AHR, airway inflammation and airway remodeling that were comparable to the 8-week model. We conclude that this new 4-week HDM model is another useful tool in studies of human asthma that offers advantages of shorter duration for development and decreased costs when compared to other models that require longer durations of exposure (5–12 weeks) to develop.